Digestibility and digestive enzyme activity in Labeo fimbriatus (Bloch, 1795) fed periphyton grown on sugarcane bagasse - Gangadhar, B.; Sridhar, N.; Umalatha, H.; Ganesh, H.; Simon, A.R.T.; Jayasankar, P. (Indian Journal of Fisheries, 2017)
An experiment of 60 days duration was carried out to compare dry matter and protein digestibility of periphyton grown on sugarcane bagasse bundles and a pelleted feed in Labeo fimbriatus (Bloch, 1795). Advanced fingerlings maintained in glass aquaria were allowed to feed on fresh periphyton or pelleted feed (20% crude protein) daily morning, the fecal matter collected following standard procedure and analysed for proximate composition. Acid insoluble ash was used as the reference marker for digestibility estimation. Activity of total protease, trypsin, chymotrypsin, carboxypeptidase - A and B, amylase, lipase and cellulase in the gut of fish was estimated at the end of the feeding trial. Periphyton and pelleted feed showed similar (p>0.05) protein digestibility (92.29 and 89.21% respectively), while total dry matter digestibility was higher (p